A randomized clinical trial on the sealing of occlusal carious lesions: 3-4-year results - Luana Severo ALVES; Fernanda Cristina Mendes de Santa GIONGO; Bruna MUA; Vanessa Balbé MARTINS; Berenice BARBACHAN E SILVA; Vibeke QVIST; Marisa MALTZ (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This randomized clinical trial aimed to assess the efficacy of sealing occlusal carious lesions in permanent teeth. The sample consisted of 54 occlusal carious lesions in permanent molars and premolars of 49 patients aged 8-43 years (median: 19 years). The inclusion criteria comprised the presence of a cavity with no access allowing biofilm control. The maximum depth of the lesion was the middle third of the dentin thickness, as assessed by bitewing radiography. The teeth were randomly assigned to sealant treatment (n = 28) or restorative treatment (n = 26). Clinical and radiographic examinations were performed after 1 year and after 3-4 years. The outcomes depended on the clinical performance of the sealant/restoration and the control of caries progression observed radiographically. Survival analysis was performed to assess success rates. Over the 3-4 years of monitoring, 2 sealants were totally lost, 1 needed repair, and 1 showed caries progression, totaling 4 failures in the sealant group. In the restoration group, 1 failure was observed (in need of repair). The success rates were 76% and 94% in the sealant and the restoration groups, respectively (p > 0.05). The sealing of occlusal carious lesions in permanent teeth succeeded in controlling caries over a 3-4-year period. However, sealed carious lesions require patient compliance in attending regular follow-ups to control the occurrence of clinical failures of the sealants.